Study Analysis of Flue Gas Utilization as Alternative Power Generation in Cement Plant Using Organic Rankine Cycle System - Rahmat Ranggonang Anwar (Jurnal Teknik ITS, 2016)
Abstract—Cement plant produce large amount of heat source in cement making process, due to inefficiency of system there still waste heat available in form of flue gas that can be utilize. Flue gas  in cement plant can be utilized as alternative power generation. With the 200-300oC temperature output range of flue gas from suspension preheater and air quenching cooler (AQC) in cement plant, organic rankine cycle (ORC) can be suitable option for alternative power generation. ORC is development of rankine cycle, the different is the working fluid in ORC using refrigerant. In cement plant that produce 8466 TPD kiln production, used flue gas from suspension preheater to dry raw material and produce 163888 m3/h flue gas from AQC that still not utilized. Flue gas with 235oC temperature from AQC can utilized for power generation purpose using ORC system. Waste heat recovery calculation carried out to know the potential recovery. Operating condition of the ORC system will determine power produced that can be generated and ORC components calculated and selected according to the operating condition of the system. Using R141b as working fluid with 8 bar pressure and 110oC temperature inlet to turbine, power produced by turbine is 666 kW. For the components, evaporator and condenser use shell and tube heat exchanger, with evaporator heat transfer area is 676.49 m2 while condenser has 510 m2 of heat transfer area. And for working fluid pump it needs 16.235 Kw power to pump R141b back to evaporator.